2001
DOI: 10.1097/00005768-200109000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Variability of competitive performance of distance runners

Abstract: Tests of endurance power suitable for assessing the smallest worthwhile changes in running performance for top runners need CV < or = 2.5% and < or = 1.5% for tests simulating half or full marathons and shorter running races, respectively. Most of the differences in variability of race times between types of race, ability groups, age groups, and sexes probably arise from differences in competitive experience and attitude toward competing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
119
3
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(129 citation statements)
references
References 6 publications
6
119
3
1
Order By: Relevance
“…The CV sets the benchmark for the smallest worthwhile change in an athlete's performance and for the typical (standard) error of measurement of tests used to assess the smallest important or worthwhile change (24). Our CV of ~2.0% at the start of the competitions and ~1.5% at the end are in line with the 1.5-1.7% reported by Hopkins and Hewson (23) and were the basis of using a ±0.5% threshold value for beneficial and harmful effects on performance (approximately 0.3 of the within-subject standard deviation top athletes show between competitions (23,24). Accordingly, there were substantial beneficial mean effects on competition performance for the female training groups compared to controls (-1.2 ±1.3%), whereas resistance training for males proved to be possibly harmful (0.5 ±1.2%).…”
Section: Discussionsupporting
confidence: 88%
“…The CV sets the benchmark for the smallest worthwhile change in an athlete's performance and for the typical (standard) error of measurement of tests used to assess the smallest important or worthwhile change (24). Our CV of ~2.0% at the start of the competitions and ~1.5% at the end are in line with the 1.5-1.7% reported by Hopkins and Hewson (23) and were the basis of using a ±0.5% threshold value for beneficial and harmful effects on performance (approximately 0.3 of the within-subject standard deviation top athletes show between competitions (23,24). Accordingly, there were substantial beneficial mean effects on competition performance for the female training groups compared to controls (-1.2 ±1.3%), whereas resistance training for males proved to be possibly harmful (0.5 ±1.2%).…”
Section: Discussionsupporting
confidence: 88%
“…Using a similar protocol to Albertus et al [29] , accurate, premature and delayed distance feedback were provided to untrained participants during 6 km treadmill TT's. In the delayed feedback trial, participants maintained a faster running velocity for longer, which enabled a 5% faster completion time, which although not statistically significant, is double the 2.5% difference deemed to be represent a meaningful change in TT performance [54] . However, this difference was in comparison to a blind feedback condition and not the accurate feedback condition, thereby supporting Albertus et al's [29] results and the perhaps more significant role of correct duration knowledge.…”
Section: Discontinuous Verbal Feedbackmentioning
confidence: 74%
“…If the smallest worthwhile difference in EP that matters to athletes is 0.5-1.5% (40,41,78,90), the present results suggest that 81-95% of the time the true effect of GIH on EP should be practically important (i.e., greater than the 0.5-1.5% level). We determined that 8 unpublished studies comparing the effect of GIH and WIH on EP would be required to reduce the ES of 0.3 to a trivial ES of 0.10.…”
Section: Measurement Of Epmentioning
confidence: 62%
“…In fact, both the percentage change in EP (2.62%) and its accompanying ES (0.35) were statistically significant. More to the point, it was observed that 81-95% of the time GIH should be associated with a small but nevertheless practically important improvement in EP if one assumes that the smallest worthwhile enhancement in performance that matters to athletes is on the order of 0.5-1.5% (40,41,78,90). One must take into account, however, that those results are derived from the data set of only 4 studies.…”
Section: Discussionmentioning
confidence: 99%